Analisis Validitas Konstruk Soal Asesmen Madrasah Bahasa Indonesia Kelas XI MA: Perspektif Taksonomi Bloom. - Albaburrahim, Albaburrahim; Khair, Febriana Nikmatul; Wachidah, Liana Rochmatul (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
Madrasah assessment questions as an evaluation instrument for learning to measure students' thinking skills need to ensure that the questions are by what will be measured and with the learning indicators. This study aims to determine the validity of the Indonesian language madrasah assessment questions in terms of the Bloom taxonomy perspective, construct and describe the role of teachers in ensuring valid questions. The method used is qualitative research with data in the form of Indonesian language assessment questions for class XI, MA Matsaratul Huda and indicators on the grid. Data analysis was carried out by comparing the suitability of the cognitive level in the assessment questions with the cognitive level in the indicators in the grid based on Bloom's taxonomy. The results of the study showed that out of ten exam questions, eight questions were valid in terms of construction because they had a match between their cognitive levels. Therefore, a re-evaluation is needed so that the questions have high quality, so that they can measure the abilities of students. This shows the importance of teachers in understanding the preparation of evaluation instruments so that learning objectives can be achieved properly.Soal asesmen madrasah sebagai instrumen evaluasi pembelajaran untuk mengukur kemampuan berpikir siswa perlu dipastikan bahwa soal tersebut sudah sesuai dengan apa yang akan diukur dan sesuai dengan indikator pembelajaran. Penelitian ini bertujuan untuk mengetahui kevalidan soal asesmem madrasah Bahasa Indonesia secara konstruk perspektif taksonomi bloom dan mendeskripsikan peran guru dalam menjamin soal yang valid. Metode yang digunakan adalah penelitian kualitatif dengan data berupa soal asesmen Bahasa Indonesia kelas XI MA Matsaratul Huda dan indikator pada kisi-kisi. Analisis data dilakukan dengan membandingkan kesesuaian level kognitif pada soal asesmen dengan level kognitif pada indikator dalam kisi-kisi yang berdasar pada taksonomi bloom. Hasil penelitian menunjukkan bahwa dari sepuluh soal ujian terdapat delapan soal yang valid secara kontruksi karena memiliki kesesuaian antara level kognitifnya. Oleh karena itu perlu adanya evaluasi kembali agar soal memiliki kualitas yang tinggi sehingga dapat mengukur kemampuan yang dimiliki siswa. Hal tersebut menunjukkan pentingnya guru dalam memahami penyusunan instrumen evaluasi agar tujuan pembelajaran dapat tercapai dengan baik.